Simian virus 40 and cancer - Sandra Eliasz; Michele Carbone; Maurizio Bocchetta (Frontiers Media S.A., 2011)
Since its discovery in 1960 as a contaminant of poliovaccines, Simian Virus 40 (SV40) has been the object of extensive studies to assess whether this oncogenic virus plays a role in human carcinogenesis. Over the last two decades, this question has met with broad scepticism. However, there is increasing evidence linking SV40 to specific types of human cancer, especially malignant mesothelioma. Recently, two laboratories using different experimental approaches independently confirmed that SV40 acts synergistically with environmental fibers to promote mesothelial cell transformation and mesothelioma. Most of the scepticism concerning SV40 and cancer was due to the lack of clear epidemiologic data. However, it is still not clear how SV40 circulates in the human population, making the identification of SV40-exposed versus non-exposed cohorts problematic. Consequently, the most helpful insights into SV40-mediated carcinogenesis have come from molecular pathology, cell and molecular biology, and from animal studies.